Glypican-3: A Novel and Promising Target for the Treatment of Hepatocellular Carcinoma - Zheng, Xiufeng; Liu, Xun; Lei, Yanna; Wang, Gang; Liu, Ming (Frontiers in Oncology, 2022)
Glypican-3 (GPC3) is a membrane-associated proteoglycan that is specifically up-regulated in hepatocellular carcinoma (HCC) although rarely or not expressed in normal liver tissues, making it a perfect diagnostic and treatment target for HCC. Several GPC3-based clinical trials are ongoing and recently several innovative GPC3-targeted therapeutic methods have emerged with exciting results, including GPC3 vaccine, anti-GPC3 immunotoxin, combined therapy with immune checkpoint blockades (ICBs), and chimeric antigen receptor (CAR) modified cells. Here, we review the value of GPC3 in the diagnosis and prognosis of HCC, together with its signaling pathways, with a specific focus on GPC3-targeted treatments of HCC and some prospects for the future GPC3-based therapeutic strategies in HCC.